Structural transformation path across Indian states: Findings from panel data analyses - Padder, Altaf Hussain; Bommayasamys, Mathavan (American Journal of Social Sciences and Humanities, 2023)
The present study aims to examine the structural transformation path across the broad economic sectors among the states of the Indian economy which is a key feature of economic development. The movement of sectoral output is a crucial regularity of the data for this study, to examine whether the middle- and low-income states have a similar structural transformation path through which the high-income states have passed, and if not, what are the characteristics of the different paths being followed. Polynomial Regression Functions were applied to fit the association between the share of sectoral output and per-capita income. The present study identified that some middle- and low-income states are following a different path of structural transformation that deviate from those of high-income states and grow faster than high-income states in the process of structural transformation, and there is great heterogeneity within each state. In the last decade, India has seen a slight dip in its services output share but only in the states of the third phase of economic transitions under the middle- and low-income groups. High-income states have shown increasing services output shares in the starting years of the first decade and then falling drastically.